Description of Extraculiculer Activities In Annur Integrated Islamic Elementry School - M. Fajar Fatkhurrahman; Yunita Mailani; M. Aris Rustam; Wanda Aura Qobidh (International Journal of Education and Teaching Zone)
Extracurricular activities in elementary school are an additional program or activity to the mandatory learning process that students must have to develop talent skills and also shape students' character. Researchers use qualitative research methods. The subjects in this study were students at the Annur Islamic Integrated Elementary School, the population in this study was taken from grades three and four, totaling 36 students. From the results of interviews and data analysis, information was obtained that extracurricular activities are activities carried out outside of class hours or outside school hours. These activities are carried out to help develop students according to their needs, talents, interests and potential. Extracurricular activities whose interests depend on the elementary school, for example drawing, coloring, karate, Scouting, painting, and also for example in integrated Islamic schools such as Tahfidz, Arabic language, English language, art, and so on. in face-to-face or face-to-face interviews and documentation which can then be analyzed and concluded. The results of this research are that of the many extracurricular activities that students are most interested in, namely extracurricular tahfidz.